Secure efficient and verifiable large linear equations solve outsourcing computing scheme - Xing-lan ZHANG; Xiang LIU (网络与信息安全学报)
A secure,efficient and verifiable outsourcing computation scheme was proposed based on the current problems of leaking users information and tampering with the calculating results,which were encountered while solving large-scale linear equations in outsourcing computation.A new linear equation with similarity solutions was constructed based on the constant transformation between random permutation and linear equations.It avoids the problem that the current data camouflage scheme is easily attacked by solving common factor method.It also improves the verification effciency and reduces the complexity of space.The performance analysis shows that the scheme is highly efficient.